O recinto fortificado romano de Casa Branca - Fabião, Carlos (2022)
Considerations about the Casa Branca fortified Roman grounds (Ferreira do Alentejo). The construction is thought to have been ephemeral and destined either to control road traffic or to lessen the instability of the earlier settlement models implemented by the Romans immediately after the pacification of Hispania.